How the islet of pigmented skin arise inside the white patches of piebaldism. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2008)
The pathogenesis of the islets of pigmented skin inside the white patches of piebaldism is not yet fully clarified, although these features are so characteristic to make the diagnosis of piebaldism easier. According to some Authors the islets of pigmentation of piebaldism are reminiscent of café-au-lait spots, although their association with neurofibromatosis type I was never shown.